Jobs and global supply chains in South-East Asia - Christian Viegelahn; Phu Huynh; Kee Beom Kim (International Labour Organization (ILO), 2023)
South-East Asia has become a key player in global supply chains (GSCs) during recent decades, and the region's participation in GSCs has had a profound impact on labour markets. This paper presents new 2000-2021 estimates of the number of GSC-related jobs in the region, with an estimated 75 million workers linked to GSCs in 2021-or more than one in four workers. Over time, the region has become increasingly dependent on GSCs for employment despite some short periods of sharp volatility and setbacks, including in 2020, the first year of the COVID-19 pandemic. The paper also presents the results of an econometric analysis, finding that the region's increased GSC participation was associated with some important, albeit mixed, progress in improving job quality. While deeper GSC integration was robustly tied to a rapid decline in working poverty and gains in labour productivity, it also shows that a positive relationship between increased GSC participation and greater wage employment, high-skill employment, and female employment was limited to specific sectors. Several policies could strengthen the links between GSCs and decent work. These include well-designed social protection and labour market policies, and investments in a broad range of skills that allow countries to shift into higher value-added segments of a value chain. Also, deep trade agreements, which increasingly include labour provisions, can help strengthen the link between increased GSC participation and decent work.
Keywords: 330; labour economics; future of work; employment; labour market; trade; COVID-19